THU0320 New Parameters for Identifying Subclinical Atherosclerosis in Patients with Primary SjöGren's Syndrome: A Pilot Study. (23rd January 2014) - Atzeni, F.; Sarzi-Puttini, P.; Gianturco, L.; Signorello, M. C.; Boccassini, L.; Ricci, C.; De Gennaro Colonna, V.; Turiel, M.
Abstract : Background: Clinical and biochemical data suggest that autoimmune diseases are associated with endothelial dysfunction and increased atherosclerosis. We have previously shown that asymmetric dimethylarginine (ADMA) levels and coronary flow reserve (CFR) are impaired in patients with early rheumatoid arthritis (1 ), but it is not known whether the same is true for patients with primary Sjögren's syndrome (pSS). Objectives: To investigate sub-clinical cardiovascular involvement in pSS patients by means of ADMA, coronary flow reserve (CFR), intima media thickness (cIMT), pulse wave velocity (PWV) and myocardial deformation. Methods: The study involved 22 outpatients with pSS (6 males, 16 females; mean age 60.14±7.81 years) and no documentable cardiovascular disease, and 22 age- and gender-matched controls. Dipyridamole transthoracic stress echocardiography was used to evaluate wall motion and CFR in the distal segment of the left anterior descending coronary artery before and after dipyridamole infusion (0.84 mg/kg over six minutes). A CFR value of <2.5 was considered a sign of impaired coronary function. We also evaluated cIMT arterial stiffness PWV and plasma ADMA levels, and made a speckle tracking echocardiography (STE) analysis. Results: All of the patients were affected by pSS and most were being treated with hydroxychloroquine (HCQ) at a dose of 400 mg/day. They were also ANA or RF and anti-SSB or anti-SSA positive. There were no significant differences in ejection fraction (EF) or E/A ratios between the patients and controls. Although within the normal range, the patients' CFR was lower than that of the controls (median 2.70; IQR 2.40-2.90 vs 3.20; IQR 3.06-3.33; p <0.0001), whereas their ADMA levels were significantly higher (median 0.81 mM; IQR 0.79-0.85 mM vs 0.54 mM; IQR 0.52-0.58 mM; p< 0.0001). Both left and right PWV values were significantly higher in the patients than in the controls (median 8.8 m/s right and 8.9 m/s left vs 6.86 and 6.89 m/s, p<0.0001), whereas cIMT was substantially similar in the two groups (0.60 mm, IQR 060-0.70 mm vs 0.60 mm, IQR 0.50-0.70, p=NS). Speckle tracking analysis was significantly different between the two groups, with longitudinal strain deformation in the apical four chambers view (Long. ɛ 4c) (median 15.28%, IQR 12.30-16.20% vs 19.80%, IQR 19.30-20.40%, p<0.0001) and radial strain deformation in short axis view (Radial ɛ SAX) (median 26.00%, IQR 24.26-31.90% vs 31.50%, IQR 28.30-34.50%, p=0.02) being significantly less in the pSS patients. Conclusions: Higher ADMA levels suggest the presence of endothelial dysfunction and sub-clinical atherosclerosis in pSS patients, even in the case of a normal CFR. This finding is supported by the PWV values, which were higher in the pSS patients. These preliminary data indicate that ADMA levels and PWV values may be useful markers for identifying early endothelial dysfunction in pSS patients. References: Turiel M, Atzeni F, Tomasoni L, et al Non-invasive assessment of coronary flow reserve and ADMA levels: a case-control study of early rheumatoid arthritis patients. Rheumatology (Oxford). 2009;48:834-9. Disclosure of Interest: None Declared